The Relationships between Self-care and Coping Strategy among People Living with Human Immunodeficiency Virus - Ibrahim, Kusman; Resnawati, Desri; Rahayuwati, Laili; Herliani, Yusshy Kurnia; Nursiswati, Nursiswati (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aims to examine the relationships between self-care and coping strategy among people living with human immunodeficiency virus (HIV) (PLWH). METHODS: A cross-sectional design involving 76 subjects of PLWH who attended the HIV clinic at a District Hospital in West Java Province, Indonesia. They met inclusion criteria such as being adult, has been living with HIV for over 1 year, and be able to communicate both verbal and written in Bahasa Indonesia. Self-care was measured by the 41-item Self-care Assessment Worksheet instrument, and coping strategies were measured by the 60-item Jalowiec Coping Scale. Pearson-product moment correlation was performed to examine the relationships between self-care and coping strategy scores. RESULTS: The majority of respondents (57.8%) used the emotion focused coping strategy such as supportant (31.5%) followed by fatalistic (21%) and optimistic (17.1%) when they deal with stressful situations. Optimistic coping was reported as the most effective coping by the respondents. Nearly half of respondents (42%) have intermediate self-care level which the highest number of self-care was medication. There was a significantly relationship between problem-focused coping strategy and the self-care scores (r = 0.378, p < 0.01). Confrontive coping strategy has positive correlation with symptoms management (r = 0.264, p < 0.05) and stress management (r = 0.280, p < 0.05). Self-care information has positive correlation with palliative coping strategy (r = 0.281, p < 0.05) and supportant coping strategy management (r = 0.236, p < 0.05). Prevention and medication have positive correlation with optimistic emotional coping strategy (r = 0.264, p < 0.05). CONCLUSION: Understanding PLWH coping strategies could assist nurses to reinforce patient’s positive coping strategies and change maladaptive coping strategies. Nurses could facilitate patients to develop a more adaptive coping strategies in enhancing self-care capability among PLWH.